2012
DOI: 10.1186/1756-6649-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the dosimetries of 3-dimensions Radiotherapy (3D-RT) with linear accelerator and intensity modulated radiotherapy (IMRT) with helical tomotherapy in children irradiated for neuroblastoma

Abstract: BackgroundIntensity modulated radiotherapy is an efficient radiotherapy technique to increase dose in target volumes and decrease irradiation dose in organs at risk. This last objective is mainly relevant in children. However, previous results suggested that IMRT could increase low dose, factor of risk for secondary radiation induced cancer. This study was performed to compare dose distributions with 3D-radiotherapy (3D-RT) and IMRT with tomotherapy (HT) in children with neuroblastoma. Seven children with neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
4
4
0
Order By: Relevance
“…To achieve good coverage with CRT, the volume receiving high dose must be large: in our study the conformity index with CRT was approximately twice that with HT and beyond compared to PBT. Other reports have shown similar results [ 12 , 13 , 20 ]. The mean dose received was considerably reduced with HT in the ipsilateral kidney thanks to the reduction of volume that received a high dose.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To achieve good coverage with CRT, the volume receiving high dose must be large: in our study the conformity index with CRT was approximately twice that with HT and beyond compared to PBT. Other reports have shown similar results [ 12 , 13 , 20 ]. The mean dose received was considerably reduced with HT in the ipsilateral kidney thanks to the reduction of volume that received a high dose.…”
Section: Discussionsupporting
confidence: 83%
“…In this study on abdominal irradiation, patients were assumed to be of uniform density for integral dose calculation [ 17 ]. The conformity index was calculated using the formula: volume of tissue receiving 95% of the prescribed dose / volume of PTV [ 12 ]. The homogeneity index was calculated using the formula: (D2% PTV–D98% PTV) / D50% PTV; where D2% PTV is the dose received by 2% of the PTV (near-maximum dose), D98% PTV is the dose received by 98% of the PTV (near-minimum dose) and D50% PTV is the median dose to PTV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series, specially conducted in women, we showed that IMRT was able to significantly avoid large tissue volumes receiving moderate to large doses at the cost of increasing the volume receiving a low dose. However, the integral dose is not increased by the IMRT technique with tomotherapy compared with 3D-CRT, as shown previously [41,75]. …”
Section: Discussionsupporting
confidence: 78%
“…However, we have already shown that the integral dose was not increased by the use of tomotherapy IMRT. 48,49 In conclusion, our study showed that IMRT is relevant in SS-NSCLC. In patients treated by a curative dose, it leads to a reduction of dose given to critical organs, allowing a better dose distribution in the tumor, and for patients treated with a preoperative schedule, our results provide the opportunity to increase the dose in future controlled trials to improve the pRC.…”
Section: Discussionsupporting
confidence: 50%